2018
DOI: 10.5897/ajb2018.16552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the chemical compositions of indigenous watermelon (Citrullus lanatus) seeds from two districts in Limpopo Province, South Africa

Abstract: Seeds from different indigenous watermelons were analysed for their chemical composition such as phenolics, proteins, oils, minerals, ash and fibre content as well as antioxidant activity measured in methanol extract using 2.2-diphenyl-1-picrylhydrazyl (DPPH) assay. The morphological variations of watermelons, which revealed diversity in terms of fruit and seed colour were also assessed. Average percentages for lipid content, total proteins, crude fibre, ash and total carbohydrates as 34.4, 16.5, 23.1, 3.99, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Rekha and Rose 21 also reported that the protein was rich in arginine, glutamic acid, aspartic acid and leucine amino acids. According to Mogotlane et al 30 , the amounts of amino acids varied significantly and leucine was found to be the most abundant amino acid, threonine was the second most abundant in water melon seed followed by methionine. Usman et al 31 reported the prevalence of glutamic acid and aspartic acid in watermelon seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Rekha and Rose 21 also reported that the protein was rich in arginine, glutamic acid, aspartic acid and leucine amino acids. According to Mogotlane et al 30 , the amounts of amino acids varied significantly and leucine was found to be the most abundant amino acid, threonine was the second most abundant in water melon seed followed by methionine. Usman et al 31 reported the prevalence of glutamic acid and aspartic acid in watermelon seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the fruit flesh, antioxidant compounds have been found in other organs of Citrullus spp. In watermelon seeds, Emmanuel et al [73] found that flavonoid content was in the range of 0.015 to 0.347 mg CE/g FW, while Adetutu et al [63] reported 0.05 mg quercetin equivalent (QE)/g FW of flavonoids. Seeds of C. colocynthis are also a source of valuable compounds, and the content of antioxidant varies among cultivars [35,74].…”
Section: Citrullusmentioning
confidence: 99%
“…Over the years, there has been an astronomical rise in prices of these commonly used oil crops, hence there is need to source for oils from underutilized or lesser known oilseeds that available to reverse the upward trend in the prices of these essential commodities. This would result in the utilisation of food-processing by-products and wastes, as well as underutilised agricultural products receiving more attention [2]. Such utilisation would contribute to maximising the available resources and result in the production of various products and foods [3].…”
Section: Introductionmentioning
confidence: 99%